Expression of multidrug transporter P‐glycoprotein in Pichia pastoris affects the host's methanol metabolism. Issue 6 (26th May 2019) - Liu, Wan‐cang; Zhou, Fei; Xia, Di; Shiloach, Joseph
Summary: Pichia pastoris KM71H (Mut S ) is an efficient producer of hard‐to‐express proteins such as the membrane protein P‐glycoprotein (Pgp), an ATP‐powered efflux pump which is expressed properly, but at very low concentration, using the conventional induction strategy. Evaluation of different induction strategies indicated that it was possible to increase Pgp expression by inducing the culture with 20% media containing 2.5% methanol. By quantifying methanol, formaldehyde, hydrogen peroxide and formate, and by measuring alcohol oxidase, catalase, formaldehyde dehydrogenase, formate dehydrogenase, malate dehydrogenase, isocitrate dehydrogenase and α ‐ketoglutarate dehydrogenases, it was possible to correlate Pgp expression to the induction strategy. Inducing the culture by adding methanol with fresh media was associated with decreases in formaldehyde and hydrogen peroxide, and increases in formaldehyde dehydrogenase, formate dehydrogenase, isocitrate dehydrogenase and α ‐ketoglutarate dehydrogenases. At these conditions, Pgp expression was 1400‐fold higher, an indication that Pgp expression is affected by increases in formaldehyde and hydrogen peroxide. It is possible that Pgp is responsible for this behaviour, since the increased metabolite concentrations and decreased enzymatic activities were not observed when parental Pichia was subjected to the same growth conditions. This report adds information on methanol metabolism during expression of Pgp from P. pastoris Mut S strain and suggests an expression procedure for hard‐to‐express proteins from P. pastoris . Abstract : Recombinant P Glycoprotein was expressed poorly in Pichia pastoris when the traditional induction procedure was implemented. By modifying the induction procedure, the expression was improved significantly (1000×). Careful analysis of metabolites and enzyme activities showed that the expressed protein affected the methanol metabolism and different induction procedure reduced this effect.